Integrated circuit quality and reliability - Hnatek, Eugene R. (a Electrical engineering and electronics, 1995)
Examines all important aspects of integrated circuit design, fabrication, assembly and test processes as they relate to quality and reliability. This second edition discusses in detail: the latest circuit design technology trends; the sources of error in wafer fabrication and assembly; avenues of contamination; new IC packaging methods; new in-line process monitors and test structures; and more. This work should be useful to electrical and electronics, quality and reliability, and industrial engineers; computer scientists; integrated circuit manufacturers; and upper-level undergraduate, graduate and continuing-education students in these disciplines.